2016
DOI: 10.1016/j.jenvp.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Walking in two French neighborhoods: A study of how park numbers and locations relate to everyday walking

Abstract: Research indicates that people are drawn to green spaces with attractive amenities. This study extends that finding by comparing walking patterns in two neighborhoods with different numbers of parks; parks did not differ in rated attractiveness nor did neighborhoods differ substantially in rated walkability. Adults, aged 32-86 years (n = 90), drew their 3 most recent walking routes on maps of their neighborhood. Analyses showed that participants' round trips were longer by 265.5 meters (.16 mile) in the neighb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 53 publications
1
15
0
1
Order By: Relevance
“…In addition, not only park availability or park size, but also other attributes of a park, or different types of public space, might be important. The literature says that specific attributes of parks such as size, facilities, safety, natural features, or maintenance are associated with walking behavior [1,2,4,6,8,36,37,38,39]. These specific factors are particularly important in planning and designing a park or station area.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, not only park availability or park size, but also other attributes of a park, or different types of public space, might be important. The literature says that specific attributes of parks such as size, facilities, safety, natural features, or maintenance are associated with walking behavior [1,2,4,6,8,36,37,38,39]. These specific factors are particularly important in planning and designing a park or station area.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, it has been suggested that a specific feature like walkability could be related to human health and wellbeing in present-day urban settings, also through increased physical activity (e.g., Brown et al, 2013; Van Cauwenberg et al, 2016). We argue that walkability and physical activity could also be influential, by working in synergy with restorative environments, and help the transition toward healthier and more sustainable lifestyles (e.g., Rioux et al, 2016). For example, we could speculate that urban planning solutions that afford walking and promote nature-based outdoor activities could also have a positive impact on promoting social inclusion and intergroup contact, thus reducing interpersonal distances across different cultural or ethnic groups (e.g., de Vries et al, 2013).…”
Section: Culture Dietary Patterns and Sustainabilitymentioning
confidence: 99%
“…A work by Rundle et al (2008), showed, for example, how access to BMI-healthy food stores is associated with lower BMI and a lower prevalence of obesity among adult residents of New York City, also controlling for neighborhood walkability. At the same time, other works have explored the link between walkability and restorative environments, showing how the presence of green spaces can increase walkability (e.g., Rioux et al, 2016), and suggesting how public open space with affordances for physical activity could be an important source for health promotion at the community level (e.g., Giles-Corti et al, 2005). Stimulating people to spend more time outside as well as being physically active and walking, could then be a tools for shifting toward more balanced, healthier, and more sustainable food consumption patterns.…”
Section: Restorative Environments and Walkability As Urban Affordancementioning
confidence: 99%
“…For example, certain recreational areas in a neighbourhood, such as urban park and blue space, have been positively related to PA and mental health, while it has been revealed that other such amenities (e.g. karaoke bar and cinema) might in fact play a negative role in generating walking behaviours [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%